MEANING OF RELIGIOUS MODERATION AND RADICALISME - Farabi, Fikri Al; Fanani, Zainuddin (ITB AAS Indonesia Surakarta, 2024)
In this context, Indonesian society faces challenges in understanding and interpreting the Islamic religion. There are two large groups in Islam, namely conservative and scripturalist groups who tend to be rigid in interpreting the teachings of the Koran, and inclusive and pluralist groups who accept differences and new traditions in accordance with the teachings of the Koran. The views of contemporary ulama, especially from the Syafi'i School of thought which is dominant in Indonesia, towards radicalism. Ulama are considered to have a key role in stemming and minimizing radicalism by prioritizing moderation in contemporary Islamic views. The concept of moderation in the context of contemporary Islamic understanding. Moderation is seen as a middle attitude that reflects justice, balance and tolerance. Some scholars, such as Sheikh Yusuf Qardhawi, teach that Islam is a moderate and balanced religion. Religious moderation, especially in contemporary Islamic views, plays an important role in dealing with radicalism. Nusantara ulama have the responsibility to minimize hardline Islamic movements by prioritizing the values of moderation, justice and balance in understanding the Islamic religion. In this way, it is hoped that Indonesia can face the challenge of radicalism in an effective way and maintain harmony between religious communities keywords: moderation, Islam